Wheat Argonaute 5 Functions in Aphid–Plant Interaction - Sibisi, Phumzile; Venter, Eduard (Frontiers in Plant Science, 2020)
Aphids feeding on plants experience similar responses to pathogens due to the prolonged and intimate contact with the plant. Diuraphis noxia is an economically important aphid pest on wheat that exhibits such an interaction. Studies on small RNA (sRNA) that regulate genes imparting resistance to wheat against D. noxia have predicted an Argonaute 5 (TaAGO5) gene as possible role player in the resistance response. Functional characterization revealed that TaAGO5 is crucial in regulating the response to infestation by D. noxia. Knockdown of TaAGO5 by 22% in D. noxia resistant wheat resulted in a completely susceptible phenotype. The fecundity and stress levels of D. noxia feeding on these silenced plants were similar to aphids feeding on the susceptible controls. Thus, TaAGO5 is crucial in the defense response by wheat plants during aphid feeding and this is similar to Nicotiana benthaminia plants experiencing arthropod herbivory. Additionally, TaAGO5 was differentially regulated by the Barley mosaic virus (BMV) used in the functional characterization. This provides evidence that TaAGO5 could play a role during virus infection of wheat. The role of AGO5 proteins in plant responses to arthropod herbivory and virus infection is known for dicotyledonous plants. Here, we present data that indicate that this role of TaAGO5 is conserved in wheat and possibly for monocotyledonous plants. These observations extend our knowledge on the roles of AGO proteins in plant resistance.